Pre-service teachers' professional becoming in an extended professional experience partnership programme. Issue 5 (20th October 2021) - Gutierrez, Amanda; Nailer, Sarah
ABSTRACT: Professional experience is viewed by governments, schools, universities and pre-service teachers as a crucial, and for some, the most important element of initial teacher education. Pre-service teachers (PSTs) consistently cite time in schools as the most valuable part of their teacher education programme. High-quality professional experience (rather than necessarily just adding days), is a priority for government and features in professional experience literature. Developing strong university–school partnerships have been suggested to provide opportunities for "quality" experiences. This paper explores the voices of PSTs with the aim of understanding what quality professional experience means, and more specifically, how experiences in an extended professional experience partnership programme enabled PSTs in the programme to become connected to the teaching profession. It appropriates Bakhtin's (1978) concept "ideological becoming" to explore the forms of connection. Findings from the PST voices in this study suggest they had significant growth in their nuanced understandings of the teaching profession which contributed to an enhanced teacher professional becoming.